Creatine O'Clock: Does Timing of Ingestion Really Influence Muscle Mass and Performance? - Darren G. Candow; Scott C. Forbes; Michael D. Roberts; Brian D. Roy; Jose Antonio; Abbie E. Smith-Ryan; Eric S. Rawson; Bruno Gualano; Hamilton Roschel (Frontiers Media S.A., 2022)
It is well-established that creatine supplementation augments the gains in muscle mass and performance during periods of resistance training. However, whether the timing of creatine ingestion influences these physical and physiological adaptations is unclear. Muscle contractions increase blood flow and possibly creatine transport kinetics which has led some to speculate that creatine in close proximity to resistance training sessions may lead to superior improvements in muscle mass and performance. Furthermore, creatine co-ingested with carbohydrates or a mixture of carbohydrates and protein that alter insulin enhance creatine uptake. The purpose of this narrative review is to (i) discuss the purported mechanisms and variables that possibly justify creatine timing strategies, (ii) to critically evaluate research examining the strategic ingestion of creatine during a resistance training program, and (iii) provide future research directions pertaining to creatine timing.